Efficient scheduling of astronomical observations: application to the CARMENES radial-velocity survey - Garcia-Piquer, Alvaro; Quirrenbach, Andreas; Seifert, Walter (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics
Gesehen am 10.10.2017